1995
DOI: 10.1259/0007-1285-68-807-271
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous fine needle puncture of the gallbladder for studies of bile composition

Abstract: Ultrasound-guided percutaneous fine needle puncture of the gallbladder (PFNP-GB) is invaluable for diagnostic and research purposes, but there are few reports about its safety. We therefore describe the efficacy and side-effects of 43 consecutive gallbladder punctures in 39 patients. PFNP-GB was successful in 40/43 (93%), but failed in three. Bile was completely aspirated in 28 of the 40 (70%) successful procedures. After 36 of the 43 punctures (84%), the patients remained asymptomatic, although on seven occas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
16
1
1
Order By: Relevance
“…Most previous studies of bile acid composition have been based on either gall bladder bile (obtained at laparotomy,30 by percutaneous gall bladder puncture31 32) or on bile rich duodenal fluid 30. In the present study we used the minimally invasive method of measuring bile acids in fasting serum.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of bile acid composition have been based on either gall bladder bile (obtained at laparotomy,30 by percutaneous gall bladder puncture31 32) or on bile rich duodenal fluid 30. In the present study we used the minimally invasive method of measuring bile acids in fasting serum.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that biliary excretion was the major elimination route for muraglitazar in humans. Other procedures for bile collection included ultrasound-guided percutaneous fine needle puncture of the gallbladder (Hussaini et al, 1995) and surgical methods such as T-tube drainage (Burnstein et al, 1982;Cheng et al, 1994). All of these methods are complicated and involve surgery, and are, thus, not readily adaptable for use in drug metabolism studies.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive techniques for bile collection involve ultrasonically guided percutaneous, sub -, or transhepatic fi neneedle puncture of the gallbladder (Hussaini et al, 1995 ;Wee et al, 1995 ), hepaticojejunostomy (Brookman et al, 1997 ), or T -tube percutaneous biliary drainage in patients after cholecystectomy (Rollins and Klaassen, 1979 ;Lorenz et al, 1984 ;J ĂŒ ngst et al, 2001 ;Ghibellini et al, 2006a and2006b ). Availability of such patients is scarce for exploratory drug studies.…”
Section: Invasive Methodsmentioning
confidence: 99%
“…Due to the surgical nature of these procedures, the possibility of infection, bile leakage, hemorrhage, and right upper quadrant pain exist (Nahrwold, 1986 ;Hosking et al, 1992 ;Williams et al, 1994 ;Hussaini et al, 1995 ;Tudyka et al, 1995 ). Also, these patients generally are on multiple coadministered drugs for treatment of their condition or to facilitate the surgical procedures, which may sometimes preclude an accurate assessment of the metabolism of the investigational drug.…”
Section: Invasive Methodsmentioning
confidence: 99%